Pengaruh Senam Aerobik Terhadap Pengurangan Nyeri Punggung Bawah Miogenik Di Rumah Sakit Islam A. Yani Surabaya - Kavita Yunanda Saphna; Sartoyo Sartoyo; Puspo Wardoyo; Achmad Fariz (Jurnal Keperawatan Muhammadiyah, 2023)
Objective:  Lack of interest doing exercise is one of the cause of myogenic low back pain caused by decreased stamina and fitness levels following muscle spasms thus resulting myogenic low back pain. One way to reduce pain  is with aerobic exercise. Methods:  This study is a pre-experimental design to determine whether there is an reduce pain by providing aerobic exercise to myogenic low back pain sufferer. The research design used in this study was a one group pretest – posttest design. This re- search was conducted on patient aged 26-45 years at Islamic Hospital of A Yani Surabaya. Aerobic Exercise was given 6 times, and pain was measured using VAS (Visual Analog Scale) test. Measurement of pain with VAS (Visual Analog Scale) test is measured when the first time patients join the riset,. The aerobic exercises given are warming up include of breathing exercise, hip movement, arm swing, flexi trunk and run in place. Second is workout include of squad, lunge variation and run in place. Third is cooling down include of stretch of the sky, squad stretch, hamstring stretch, hip flexor and breathing exercise. The frequency of exercise given is 2 times a week for three weeks with an intensity of 6 repetitions per set, and held for 8 seconds. Posttest data retrieval was carried out again for all patients after undergoing aerobic exercise 6 times using VAS (Visual Analog Scale) test.Results:   The composite value of VAS (Visual Analog Scale) test on posttest results after giving 6 times of aerobic exercise is quite significant compared to the results of pretest before giving aerobic exercise. The data was tested for normality using the Chi-squared test with the results obtained were P <0.05, which means there is a statistically significant relationship between the two variables.Conclusion:  The results obtained in the study showed pain reduction from patient with myogenic low back pain after being given aerobic exercise.